Nucleic Acids From Basic Aspects to Laboratory Tools - Larramendy, Marcelo L.; Soloneski, Sonia (IntechOpen, 2016)
This edited book, "Nucleic Acids - From Basic Aspects to Laboratory Tools", contains a series of chapters that highlight the development and status of the various aspects of the nucleic acids related to DNA chemistry and biology and the molecular application of these small DNA molecules and related synthetic analogues within biological systems. Furthermore, it is hoped that the information in the present book will be of value to those directly engaged in the handling and use of nucleic acids, and that this book will continue to meet the expectations and needs of all who are interested in the different fascinating aspects of molecular biology.